Growth and coarsening kinetics of gamma prime precipitates in CMSX-4 under simulated additive manufacturing conditions. (November 2019) - Wahlmann, Benjamin; Galgon, Florian; Stark, Andreas; Gayer, Sören; Schell, Norbert; Staron, Peter; Körner, Carolin
Abstract: Additive manufacturing of superalloys offers new opportunities for alloy design but also poses significant processing difficulties. While the γ′ phase is responsible for the excellent high-temperature resistance of these alloys, it also induces cracking by precipitation hardening during manufacturing. Using small-angle X-ray scattering, we characterized the dynamic precipitation, dissolution, coarsening, and morphological evolution of the γ′ phase in situ during simulated additive manufacturing conditions. For this purpose, a CMSX-4 cylinder was subjected to cyclic heat treatment with heating and quenching rates up to 300 K/s. A specialized setup employing aluminum lenses to focus the X-ray beam was utilized to extend the q-range to small scattering vectors up to 0.035 nm −1 . It was shown that the γ′ phase precipitates extremely fast without any measurable undercooling but remains below the equilibrium fraction throughout the process. Coarsening is readily measurable over timespans of only several seconds. A fraction of the γ′ phase that was dissolved during heating reprecipitated by forming new particles instead of growing on already existing precipitates. The findings provide new insight into the dynamic behavior of the γ′ phase during additive manufacturing and may prove valuable in designing new superalloys and processing strategies for additive manufacturing. Graphical abstract: Image 1